Green criminological perspectives on dog-fighting as organised masculinities -based animal harm - Nurse, Angus (Trends in organized crime, 2021)
Dog-fighting was historically a working-class pursuit within predominantly white, working-class subcultures, representing a distinct type of organised animal exploitation. However, contemporary dog-fighting has moved way from its organised pit-based origins to encompass varied forms of organised activity including street dog-fighting in the form of chain fighting or chain rolling, the use of dogs as status or weapon dogs. This paper examines dog-fighting from a green criminological perspective as a distinct form of organised and subcultural crime. Analysis of UK legislation identifies that the specific offence of ‘dog-fighting’ does not exist. Instead, dog-fighting is contained within the ‘animal fighting’ offence, prohibited by provisions of the Animal Welfare Act 2006. However, beyond the actual fight activities (pitting dogs against each other or attacking humans), a range of other offences are associated with dog-fighting including: illegal gambling; attending dog-fighting events; animal welfare harms; and the breeding and selling of dogs for fighting. This paper’s analysis examines contemporary legal perspectives on such activities; also discussing how illegal fieldsports (e.g. dog-fighting and cock-fighting) are dominated by organised crime elements of gambling and distinctly masculine subcultures through which a hierarchy of offending is established and developed. Commensurate with previous research that identifies different offender behaviours and offending within animal crime, this paper concludes that variation exists in the nature of dog-fighting to the extent that a single approach to offenders and offending behaviour is unlikely to be successful.